Review of the Calculations Cost of Production and Selling Price in Rumah Tempe Indonesia - Jasmadeti; Amrulloh; Siti Zahratun Fardilah (International Journal of Advanced Technology and Social Sciences, 2023)
One of the problems that is often faced by MSMEs is the calculation of production time which makes management look bad. The calculation of the cost of production is very helpful in determining the selling price of a product, so the company must calculate the cost of production first. After the cost of production is obtained, the company can determine the selling price of the products sold to customers. Determining the selling price that is not right can cause losses if the selling price is too low and cannot cover the production costs that have been incurred. The location that is the object of this review is Rumah Tempe Indonesia. This research is expected to provide an overview of the calculation of the cost of goods manufactured and the determination of the selling price correctly in accordance with applicable accounting rules. Rumah Tempe Indonesia (RTI) is one of the MSMEs involved in the tempe processing industry which is owned by KOPTI Bogor Regency. The results of this review indicate that the cost of production of tempe bacem according to Rumah Tempe Indonesia is not in accordance with cost accounting standards so that the selling price is set lower than the selling price calculated according to cost accounting standards. The calculation of the cost of production carried out by Rumah Tempe Indonesia is not yet detailed, so the profit generated is not maximized. The calculation of the selling price used by Rumah Tempe Indonesia is also not correct because the price set is in accordance with market competition prices while the selling price calculation is according to accounting standards which is higher than the calculation of Rumah Tempe Indonesia